Experimental and Numerical Study of Flow Through Horizontal Wellbore of the 180 Perforation Phasing - Mustafa, Mohammed A.; Rishack, Qais A.; Abdulwahid, Mohammed A. (Basrah Journal for Engineering Sciences, 2022)
This paper demonstrates experimental and numerical studies to investigate in perforation pipes with a phasing 180° and perforation densities 9 spm in a horizontal wellbore. The experimental study was conducted to investigate the phasing angle 180° in a horizontal wellbore. The wellbore has an inner diameter of 44 mm, as well as the length of the pipe is 2 m. For this purpose, a simulation model was created in the wellbore using the ANSYS FLUENT simulation software by using the standard k - e model and applied to the (CFD) with changing the axial flow from (40 - 160) lit/min and constant inflow through perforations from range (20 - 80) lit/min. Concerning the findings of this study, it was noticed that the total pressure drop (friction, acceleration, mixing) goes high as the total flow rate ratio increases. As well as, an increase of the inflow concerning the main flow rate ratio leads to an increase in the total pressure drop and a decrease in the productivity index. Furthermore, the percentage error of the total pressure drop between the numerical and experimental results in test 4 is about 5.4 %. Also, the average velocity goes high with increasing the total flow rates and the velocity keeps increasing along the length of the pipe until it reaches its maximum value at the end of the pipe due to the effect of the perforations. It was concluded that there are the numerical and experimental results reflected a good agreement concerning the study of the flow-through perforations at 180° angle in terms of pressure drop and apparent friction factor, etc.